Synthesis of Nucleosides and Non-nucleosides Based 4,6-disubstituted-2-oxo-dihydropyridine-3-carbonitriles as Antiviral Agents - Ibrahim, Tarek S.; El-Sayed, Hassan A.; Khayat, Maan T.; AL-Mahmoudy, Amany M.M.; Moustafa, Ahmed H.; El-Deen, Ayat K.S.; Rostom, Sherif A.F.; Panda, Siva S. (Medicinal Chemistry, 2018)
Background: Viral diseases are considered main threats that face the humanity worldwide. The emergence of new viruses like influenza viruses emphasizes the significance of designing novel antiviral drugs. Method: The aim of this work is to synthesize a new set of nucleoside and non-nucleoside cyanopyridine, characterized and evaluated for their in vitro antiviral properties against various strains. Conclusion: More of the compounds showed variable antiviral potential against a panel of eighteen DNA and RNA viruses. The screening data suggested that the order of activity of the active compounds are in the order of O-glycosyl > O-alkyl > N-alkyl > S-alkyl derivatives. In addition, the 4-fluoro substituted compounds are more effective among the O- and N-alkyl analogs, whereas remarkable antiviral activity was ascribed to the methoxylated O-glycosyl derivatives. Most of the active compounds proved to be more selective towards the inhibition of the replication of DNA rather than the RNA-viruses. The analogs 1a, 2a, 12b, 14b and 16b possessed broad spectrum and noticeable antiviral potential against most of the tested DNA- and RNA-viruses (EC50 ≈ 0.8-20 μM), accompanied with considerably low cytotoxic margin (MCC ≈ 4-20 μM), and comparable with reference standard antiviral agents.
Keywords: Synthesis